Exploring the Pharmacological Potential of Onosma riedliana: Phenolic Compounds and Their Biological Activities - Ćavar Zeljkovıć, Sanja; Sahinler, Saliha Seyma; Sarikurkcu, Cengiz; Kirkan, Bulent; Binzet, Riza; Tarkowski, Petr (Plant foods for human nutrition, 2024)
Onosma riedliana Binzet & Orcan, a traditionally used plant species, has been explored for its therapeutic potential in this study. The work presented here is the first report on the phenolic profile and biological activity of this species. Three extracts of varying polarity were prepared, with the methanolic extract containing the highest phenolic content (97.62 ± 0.20 mgGAE/g). Key phenolic compounds identified included pinoresinol, hesperidin, 4-hydroxybenzoic acid, and p-coumaric acid. The methanolic extract exhibited exceptional antioxidant properties, rivaling Trolox as a positive control, primarily attributed to hesperidin and luteolin. Moreover, the ethyl acetate extract demonstrated remarkable inhibition of cholinesterase and tyrosinase enzymes, while the methanolic extract displayed potent activity against carbohydrate hydrolytic enzymes, α-amylase and α-glucosidase. Again, phenolic compounds were shown to be responsible for the inhibition of cholinesterases and tyrosinase, but not for α-amylase and α-glucosidase. These findings underscore Onosma riedliana's potential for incorporation into diverse pharmaceutical formulations, given its multifaceted bioactivity.
Keywords: Hesperidin; Monophenol Monooxygenase; tyrosinasa; alpha-Glucosidases; methanol; alfa-amylasy; rostlinné extrakty; antioxidancia; alpha-Amylases; Plant Extracts; Phenols; Enzyme Inhibitors; Antioxidants; fenoly; inhibitory enzymů; alfa-glukosidasy; Methanol; hesperidin